2002
DOI: 10.2307/3079314
|View full text |Cite
|
Sign up to set email alerts
|

Deterministic Limits to Stochastic Spatial Models of Natural Enemies

Abstract: Stochastic spatial models are becoming an increasingly popular tool for understanding ecological and epidemiological problems. However, due to the complexities inherent in such models, it has been difficult to obtain any analytical insights. Here, we consider individual-based, stochastic models of both the continuous-time Lotka-Volterra system and the discrete-time Nicholson-Bailey model. The stability of these two stochastic models of natural enemies is assessed by constructing moment equations. The inclusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Among the several theoretical descriptions of population biology systems, the stochastic approach is one capable of revealing the ubiquitous fluctuations observed in these systems [1,2,3,4,5]. Using a stochastic lattice gas model, we study here the dynamics of propagation of an epidemic in a population in which the individuals are separated into three classes determined by their relative states to a given disease: susceptible (S), infected (I) and recovered (R) individuals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the several theoretical descriptions of population biology systems, the stochastic approach is one capable of revealing the ubiquitous fluctuations observed in these systems [1,2,3,4,5]. Using a stochastic lattice gas model, we study here the dynamics of propagation of an epidemic in a population in which the individuals are separated into three classes determined by their relative states to a given disease: susceptible (S), infected (I) and recovered (R) individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Using a stochastic lattice gas model, we study here the dynamics of propagation of an epidemic in a population in which the individuals are separated into three classes determined by their relative states to a given disease: susceptible (S), infected (I) and recovered (R) individuals. One of the most well known models in this context is the socalled susceptible-infected-recovered (SIR) model [1,2,3,4,5,6,7,8,9,10,11,12,13], a model for an epidemic which occurs during a time interval that is much smaller then the lifetime of the host. It describes the spreading of an epidemic process occurring in a population initially composed by susceptible individuals that become infected by contact with infected individuals.…”
Section: Introductionmentioning
confidence: 99%
“…that movement rates are of the same magnitude as vital rates. Keeling et al (2002) formulated moment equation models for systems with limited movement using a framework similar to ours. They assumed independent movement and found that the system is stabilized if predators move approximately six times faster than the prey.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Keeling et al (2002) evaluated the dynamical effects of limited movement rates by decreasing these rates. However, this violates the approximation and at some point, the model will break down.…”
Section: Discussionmentioning
confidence: 99%
“…This led to the development of numerous methods, ranging from simple mean-field approximations to moment closure techniques, for simplifying and analysing individualbased models (Durrett and Levin, 1994a;Rand, 1999;Keeling et al, 2002). In the simplest of individual-based models-where although there are discrete, separate interaction sites there is no spatial structure and interactions are simple births and deaths-a relationship can be shown between the individual-based model and an appropriately chosen deterministic dynamical system.…”
Section: Introductionmentioning
confidence: 99%